Blockage of TNF-α by Infliximab Reduces CCL2 and CCR2 Levels in Patients With Rheumatoid Arthritis. (1st August 2011) - Xia, Liping; Lu, Jing; Xiao, Weiguo
Abstract : Objectives: To investigate the mechanism in vivo for the regulation of inflammation of patients with RA by infliximab, we measured serum levels of chemokine ligand (CCL) 2, CCL3, CXCL8, and expression of CCL2 receptor chemokine receptor (CCR) 2 on CD4 + T cells from patients with rheumatoid arthritis (RA). Methods: Forty-four patients with were enrolled in our study. Twenty-four patients received infliximab combined with methotrexate. Twenty patients received methotrexate alone. Serum levels of the chemokines CCL2, CCL3, and CXCL8 were quantified using commercial enzyme-linked immunosorbent assay kits. Flow cytometry was used to analyze the expression of CCR2 on CD4 + T cells. Results: The mean CCL2 levels in the infliximab-treated patients decreased significantly from 885.20 ± 323.52 pg/mL at pretreatment to 454.65 ± 185.03 pg/mL ( P < 0.05) at 30 weeks after the initial treatment. Fluorescence density of CCR2 expression on CD4 + T cells were significantly reduced after infliximab treatment. Conclusions: CCL2/CCR2 system in patients with active RA may be sensitive to anti-tumor necrosis factor-α therapy and suggest that CCL2 plays a crucial role in the pathogenesis of RA. CCR2 may be an important target for therapy in RA.